The Role of Social Science in Successfully Implementing Watershed Management Strategies. (April 2015) - Floress, Kristin; Akamani, Kofi; Halvorsen, Kathleen E.; Kozich, Andrew T.; Davenport, Mae
Abstract Successful watershed management and changes in water quality conditions are dependent upon changes in human behaviors. Those tasked with managing watersheds and other natural resources often assume that people are not acting to protect or restore their resources because they lack the necessary knowledge and understanding. However, individual behaviors are impacted by a variety of social, psychological, institutional, and economic factors that need to be understood for successful implementation of watershed management strategies. This paper provides an introduction to the field of human dimensions of watershed management, an overview of social science concepts that have been found to explain water‐related behaviors, and how social information can be translated into actionable items in a management plan.